Influence of Martian regolith analogs on the activity and growth of methanogenic archaea, with special regard to long-term desiccation - Schirmack, Janosch; Alawi, Mashal; Wagner, Dirk (Frontiers in Microbiology, 2015)
Methanogenic archaea have been studied as model organisms for possible life on Mars for several reasons: they can grow lithoautotrophically by using hydrogen and carbon dioxide as energy and carbon sources, respectively; they are anaerobes; and they evolved at a time when conditions on early Earth are believed to have looked similar to those of early Mars. As Mars is currently dry and cold and as water might be available only at certain time intervals, any organism living on this planet would need to cope with desiccation. On Earth there are several regions with low water availability as well, e.g. permafrost environments, desert soils and salt pans. Here, we present the results of a set of experiments investigating the influence of different Martian regolith analogs on the metabolic activity and growth of three methanogenic strains exposed to culture conditions as well as long-term desiccation. In most cases, concentrations below 1 %wt of regolith in the media resulted in an increase of methane production rates, whereas higher concentrations decreased the rates, thus prolonging the lag phase. Further experiments showed that methanogenic archaea are capable of producing methane when incubated on a water-saturated sedimentary matrix of regolith lacking nutrients. Survival of methanogens under these conditions was analyzed with a 400 day desiccation experiment in the presence of regolith analogs. All tested strains of methanogens survived the desiccation period as it was determined through reincubation on fresh medium and via qPCR following propidium monoazide treatment to identify viable cells. The survival of long-term desiccation and the ability of active metabolism on water-saturated MRAs strengthens the possibility of methanogenic archaea or physiologically similar organisms to exist in environmental niches on Mars. The best results were achieved in presence of a phyllosilicate, which provides insights of possible positive effects in habitats on Earth as well.